Evaluation of Postoperative Analgesia of DexmedetomidineAlone or Associated to Morphineas Premedicants in Bitches Undergoing Ovariosalpingohisterectomy - Fernandes da Costa, Tais Aroma; de Mascarenhas, Lívia Caroline; da Anunciação Filho, Wellington Monteiro; Araújo Sônego, Dábila; Dilda Campos, Giulia Maria; Pinto Ribeiro, Alexandre; Niederauer Flores, Fabiola; Dambrósio Guimarães, Luciana (Acta Scientiae Veterinariae, 2019)
Background:Elective ovariossalpingohysterectomy is a common surgery that causes mild to moderate pain. Aiming at the treatment of pain in these patients, analgesia should be balanced from pre-anesthetic, transoperative and postoperative medication, with α-2-agonists and opioids being commonly used, especially dexmedetomidine that has sedation, relaxation muscle and analgesia. The aim of the present study was to evaluate the postoperative analgesic efficacy of dexmedetomidine alone and associated with morphine when used in the preanesthetic medication of bitches submitted to elective ovarian oysterectomy using the modified Glasgow pain scale and the Melbourne pain scale. Materials,Methods & Results:Twenty bitches were used in this study, all of them submitted to ovarian oysterectomy, and were clinically healthy according to laboratory and clinical exams. During the experiment, bitches were randomly distributed into two groups, which received preanesthetic medication (MPA) with 5μg/kg dexmedetomidine alone (GD) or associated with 0.3 mg/kg morphine (GDM) intramuscularly (IM). In both groups, anesthetic induction with dose-effect propofol was performed and maintained with isoflurane diluted in 100% oxygen administered through a calibrated vaporizer and appropriate anesthetic system based on the weight of the animal and maintained on spontaneous ventilation. After stabilization of the patient the surgery was started, which lasted 45 min. The bitches were evaluated by the Modified Glasgow Scale (GSM), the Melbourne Scale (MS) and the Dobbins Sedation Scale (DS), previously administered MPA (T0) and the others performed in 1h (T1), 2h (T2), 4h (T3), 8h (T4), 12h (T5) and 24h (T6) after extubation. If the GSM score was greater than the value of 3.3 an analgesic rescue of 0.5 mg/kg of morphine intramuscularly would be administered. An increase in the scoring of pain scales in both groups can be observed from the T1, with significant difference only of the T1 in relation to the T0 in the GSM of the GDM. Two rescues were performed in T1 of GD and three rescues in T1 and a rescue in T3 of GDM. There was no significant difference between the groups in relation to this variable, as a result of P = 0.62. Discussion:Based on the results of this study, dexmedetomidinedoes not have adequate analgesic effect for use in preemptive analgesia of bitches submitted to elective OSH due to the high number of analgesic rescues. A small increase in GSM and MS scores from T1 can be expected compared to values prior to the surgical procedure since there was no nociceptive stimulation. This increase was only significant in T1 of GDM, moment of greatest rescue number (n = 3). The absence of significant difference between the groups proves that the analgesic effect of dexmedetomidine was not potentiated by the association with morphine at the dose and route used in this experiment. Although morphine is widely used and proven to be effective for the surgical procedure of ovariossalpingohysterectomy, both when used alone and in combination with other drugs, this fact has not been proven in the present study. This fact may have occurred due to the low dose of dexmedetomidine used or due to its short duration. Therefore, dexmedetomidine at the dose used as preanesthetic medication did not produce an adequate analgesic effect in the postoperative period of bitches submitted to elective ovariossalpingohysterectomy. The effects of the same were not potentiated by the association with morphine, at the dose used. Not being recommended for postoperative analgesic control of electiveovariossalpingohysterectomy in bitches. However, further studies are needed to better evaluate the analgesic effect of this α-2-agonist.